Proceso de atención de enfermería en paciente adulto mayor con broncoectasia - Naranjo Tobar, Farina Fabiola (2021)
The clinical case study shows an older adult to whom the nursing care process applies, with a personal history of pneumonia, bronchitis, which goes to the emergency area for coughing with mucopurulent expectoration, medium-effort dyspnoea, and 38.5C hyperthermia, is entered with oxygen support by simple mask at 4 liters per minute with vital blood pressure signs 138/88 mmHg, heart rate 100 Ply, breathing rate: 24 Rpm, temperature: 38.5oC, Oxygen saturation: 94% is assessed by treating physician where laboratory tests were requested, anterior poster chest x-ray with findings of increased interstitial markings, thickening of bronchial walls and pulmonary bloating , in addition, complete hematic biometrics was requested with VDRL test, after obtaining the results is diagnosed with Bronchiectasia secondary to recurrent pneumonia, the medication given to the patient was Sodium Chloride 0.9% 500 ml iv at 42 ml/hour, omeprazole 40 mg iv each day, oral support every day, acetaminophen 1 gram every 8 hours, wet oxygen by simple mask and aspiration of secretions a thermal rise of 38 degrees corrected with 1000 mg of acetaminophen immediately, the measures taken were the control of vital signs, aspiration of secretions, and administration of medicines, the patient receives hospital discharge under stable clinical conditions at the sixth day of his hospitalization.